Highly efficient and automated extraction of DNA from human remains using a modified EZ1 protocol - Anna Barbaro; Sasha Samar; Giacomo Falcone; Angelo La Marca (Oxford University Press, 2021)
Bones and teeth often represent the only sources of DNA available for identifying human remains. DNA in bones and teeth is generally better preserved than that in soft tissues because of the presence of hard connective tissue with a high level of calcium. Because of the extensive mineralisation, the choice of an efficient DNA extraction procedure is important to minimise the sampling of a high level of minerals and to remove polymerase chain reaction (PCR) inhibitors. Some protocols are available for DNA extraction from bones and teeth as part of the Qiagen EZ1 DNA Investigator Kit using the EZ1 Advanced XL automated purification platform. To improve the efficiency of DNA extraction from skeletal remains, the present study focuses on a modification to these already available protocols. In this study, different bones and teeth collected between 1 and 50 years after death were subjected to DNA extraction using the standard EZ1 protocol, a supplementary protocol, and a modified protocol. The modified approach included a decalcification step, whereas the Qiagen protocols worked directly on non-decalcified powder. In all three procedures, 150 mg samples were used for DNA extraction. We evaluated the quantity of DNA recovered from samples, the presence of any PCR inhibitors co-extracted, the level of DNA degradation, the quality of short tandem repeat (STR) profiles, and the reproducibility of the modified procedure. When compared with the other protocols, the modified protocol resulted in the best recovery of DNA that was free of PCR inhibitors. Additionally, the STR profiles were reliable and of high quality. In our opinion, the decalcification step increases DNA recovery by softening tissues, which allows lysis solutions to act more effectively. Furthermore, the use of two lysis solutions and the variation added to the EZ1 purification step allow for DNA recovery with quality and quantity superior to those of the previously available Qiagen-based protocols. These findings may be helpful solutions to the problems commonly encountered when dealing with difficult samples, such as bones and teeth.Key points Bones and teeth often represent the only sources of DNA for identifying human remains. The choice of an efficient DNA extraction procedure is important for maximizing DNA recovery and removing PCR inhibitors. This study focuses on modifications to the previously available Qiagen-based protocols. The modified protocol enabled the best recovery of DNA, and both quality and quantity were superior to those of the previously available Qiagen-based protocols. The STR profiles obtained from samples extracted using the modified protocol were reliable and of high quality.